2021
DOI: 10.1073/pnas.2012386118
|View full text |Cite
|
Sign up to set email alerts
|

A lower-than-expected saltation threshold at Martian pressure and below

Abstract: Aeolian sediment transport is observed to occur on Mars as well as other extraterrestrial environments, generating ripples and dunes as on Earth. The search for terrestrial analogs of planetary bedforms, as well as environmental simulation experiments able to reproduce their formation in planetary conditions, are powerful ways to question our understanding of geomorphological processes toward unusual environmental conditions. Here, we perform sediment transport laboratory experiments in a closed-circuit wind t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 72 publications
(177 reference statements)
8
65
1
1
Order By: Relevance
“…An empirical scaling relation that is consistent with experimental data is where c e is a proportionality constant close to unity (Beladjine et al, 2007). Figure 8e shows model predictions of Θ cont , using Equations 26, 27a, and 27b with c e = 0.8, and compares them with measurements of Θ cont for aeolian NST (Andreotti et al, 2021;Carneiro et al, 2015;Ho, 2012;Martin & Kok, 2018). Note that Andreotti et al (2021) carried out their experiments in a wind tunnel with varying air pressure and defined threshold conditions as the transition between saltation of groups of particles (bursts) to intermittent saltation of single particles (at high pressure) or no transport (at low pressure).…”
Section: Continuous Transport Thresholdsupporting
confidence: 65%
See 3 more Smart Citations
“…An empirical scaling relation that is consistent with experimental data is where c e is a proportionality constant close to unity (Beladjine et al, 2007). Figure 8e shows model predictions of Θ cont , using Equations 26, 27a, and 27b with c e = 0.8, and compares them with measurements of Θ cont for aeolian NST (Andreotti et al, 2021;Carneiro et al, 2015;Ho, 2012;Martin & Kok, 2018). Note that Andreotti et al (2021) carried out their experiments in a wind tunnel with varying air pressure and defined threshold conditions as the transition between saltation of groups of particles (bursts) to intermittent saltation of single particles (at high pressure) or no transport (at low pressure).…”
Section: Continuous Transport Thresholdsupporting
confidence: 65%
“…Figure 8e shows model predictions of Θ cont , using Equations 26, 27a, and 27b with c e = 0.8, and compares them with measurements of Θ cont for aeolian NST (Andreotti et al, 2021;Carneiro et al, 2015;Ho, 2012;Martin & Kok, 2018). Note that Andreotti et al (2021) carried out their experiments in a wind tunnel with varying air pressure and defined threshold conditions as the transition between saltation of groups of particles (bursts) to intermittent saltation of single particles (at high pressure) or no transport (at low pressure). These authors interpreted their measurements as measurements of the transport threshold Θ t , that is, they assumed Θ cont = Θ t .…”
Section: Continuous Transport Thresholdmentioning
confidence: 99%
See 2 more Smart Citations
“…(1987) that showed that a population of small ripples had a stable size under a wide range of atmospheric pressures, without significant changes in wavelength, whereas a second population of ripples grew in size with decreasing atmospheric pressure. Similarly, recent low‐pressure wind‐tunnel experiments also have demonstrated the characteristic wavelength of small impact ripples do not change substantially as atmospheric pressure is changed from terrestrial to Martian values (Andreotti et al., 2021; Claudin et al., 2020).…”
Section: Figurementioning
confidence: 92%